Federal judge ideology, securities class action litigation, and stock price crash risk - Cui, Xiaoyu; Han, Jianlei; Kim, Jeong Bon; Qi, Baolei (Accounting and finance (Parkville), 2024)
This study investigates whether and how federal judge ideology affects firm‐specific stock price crash risk. Using a comprehensive sample of US firms, we find a decline in the likelihood of future stock price crashes for firms headquartered in more liberal circuits. In identifying potential mechanisms, we show that liberal judge ideology reduces information opacity, risk‐taking behaviours and overinvestment, and thus curbs stock price crash risk. Furthermore, the curbing effect is more salient for firms with poor monitoring quality and those in low social capital areas. Overall, this study elucidates how federal judge ideology affects capital markets.